Tuning the Optical Properties of 2‐Thienylpyridyl Iridium Complexes through Carboranes and Anions. Issue 12 (6th February 2015) - Zhu, Lin; Tang, Xiao; Yu, Qi; Lv, Wen; Yan, Hong; Zhao, Qiang; Huang, Wei
Abstract 2‐Thienylpyridyl iridium(III) complexes containing an o‐, m‐, or p‐carboranylvinyl‐2, 2′‐bipyridine ligand and various counteranions (denoted o‐PF6, m‐BF4, m‐PF6, m‐SbF6, m‐ClO4, m‐OTf, m‐NO3, m‐BPh4, m‐F, m‐Cl, and p‐PF6) were synthesized by using C‐formyl carboranes as starting materials. The solid‐state structures of o‐PF6, m‐PF6, m‐ClO4, and m‐BF4 showed that the cations form twisted cavities in which the anions are fixed by multiple hydrogen bonds. Anion–hydrogen interactions were investigated for nine m‐carborane‐based complexes with different counteranions. All carborane‐based iridium(III) complexes show similar phosphorescence yields in solution but significantly different emission in the solid state. Anion‐exchange titration and theoretical calculations revealed the relationships between structures and optical properties. The size of the anion and CH⋅⋅⋅X anion–hydrogen bonds strongly influence the phosphorescence quantum yield in the solid state. In particular, the CcarH⋅⋅⋅X hydrogen bonds between the carboranyl unit and the anion play an important role in solid‐state phosphorescence. Complex p‐PF6 was successfully applied in phosphorescence‐lifetime bioimaging owing to its low toxicity and near‐infrared emission.